2020
DOI: 10.1096/fj.201901902rr
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood CD163(+) monocytes and soluble CD163 in dry and neovascular age‐related macular degeneration

Abstract: Macrophages are the main infiltrating immune cells in choroidal neovascularization (CNV), a hallmark of the human wet, or neovascular age‐related macular degeneration (AMD). Due to their plasticity and ability to adapt to the local microenvironment in a tissue‐dependent manner, macrophages display polar functional phenotypes characterized by their cell surface markers and their cytokine profiles. We found accumulation of hemoglobin‐scavenging cluster of differentiation 163 (CD163)(+) macrophages in laser‐induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…[162][163][164] M2-like macrophages produced MMPs, which enhanced the penetration of CNV through Bruch's membrane, while M1 macrophages ameliorated CNV. [165][166][167][168][169] Previous studies also showed that CNV could be inhibited by downregulating M1 macrophage/microglia polarization. 170 Allingham et al suggested that the early recruitment of inflammatory M1 macrophages promoted the induction and initial development of CNV, followed by the sustained recruitment of reparative M2 macrophages that mediated the sustained CNV formation and growth.…”
Section: Lcpufa Peroxidation and Its Effects On Inflammation In Amdmentioning
confidence: 99%
“…[162][163][164] M2-like macrophages produced MMPs, which enhanced the penetration of CNV through Bruch's membrane, while M1 macrophages ameliorated CNV. [165][166][167][168][169] Previous studies also showed that CNV could be inhibited by downregulating M1 macrophage/microglia polarization. 170 Allingham et al suggested that the early recruitment of inflammatory M1 macrophages promoted the induction and initial development of CNV, followed by the sustained recruitment of reparative M2 macrophages that mediated the sustained CNV formation and growth.…”
Section: Lcpufa Peroxidation and Its Effects On Inflammation In Amdmentioning
confidence: 99%
“…Macrophages are the primary infiltrating immune cells in choroidal neovascularization (CNV), a hallmark of exudative AMD [126]. Higher levels of MCP‐1 have been identified in the serum of patients with exudative AMD compared with unaffected age‐ and gender‐matched controls [127].…”
Section: Age‐related Macular Degenerationmentioning
confidence: 99%
“…The monocyte marker CD163, along with other cytokines implicated in inflammation, may be an indicator of disease status in AMD. The levels of multiple cytokines including CD163 in the peripheral blood of human patients differed between exudative AMD, nonexudative AMD, and age‐matched controls, depending on the presence of active leakage in exudative cases [126]. Higher peripheral blood levels of C‐reactive protein and IL‐6, for example, have been associated with AMD progression [129,130].…”
Section: Age‐related Macular Degenerationmentioning
confidence: 99%
“…The therapeutic effect of CHA is due to repolarization of M2 macrophages to M1. Plasticity and mobility are hallmarks of TAMs [84], and TAMs can be remodeled by a CHA‐educated TME. CHA therapy for patients with glioma can skew the macrophages in the TME away from the M2 phenotype and toward the M1 phenotype by stimulating STAT1 and repressing the STAT6 signal pathway.…”
Section: Immunotherapy Targeting Tams In the Treatment Of Gliomasmentioning
confidence: 99%